2023
DOI: 10.1186/s12967-023-04008-7
|View full text |Cite
|
Sign up to set email alerts
|

Muscle distribution in relation to all-cause and cause-specific mortality in young and middle-aged adults

Abstract: Background The relationship between muscle and prognosis, especially that between muscle distribution across different body parts, and the related prognosis is not well established. Objective To investigate the relationship between muscle distribution and all-cause and cause-specific mortality and their potential modifiers. Design Longitudinal cohort study. C-index, IDI, and NRI were used to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Based on previous studies of the association between body composition and mortality [ 34 , 35 ], we included a variety of covariates that could potentially influence the outcome. These included age (as a continuous variable), gender (male or female), race (categorized into non-Hispanic White, non-Hispanic Black, Mexican American, and other races, the other races includes Multi-Racial individuals), smoking status (current smoker, former smoker, never smoked), alcohol drinking status (current drinker, former drinker, non-drinker), income-to-poverty ratio (PIR) (a continuous variable), and multiple disease conditions (including self-reported heart failure, coronary heart disease, hypertension, renal failure, liver conditions, diabetes, stroke, heart attack, and cancer).…”
Section: Methodsmentioning
confidence: 99%
“…Based on previous studies of the association between body composition and mortality [ 34 , 35 ], we included a variety of covariates that could potentially influence the outcome. These included age (as a continuous variable), gender (male or female), race (categorized into non-Hispanic White, non-Hispanic Black, Mexican American, and other races, the other races includes Multi-Racial individuals), smoking status (current smoker, former smoker, never smoked), alcohol drinking status (current drinker, former drinker, non-drinker), income-to-poverty ratio (PIR) (a continuous variable), and multiple disease conditions (including self-reported heart failure, coronary heart disease, hypertension, renal failure, liver conditions, diabetes, stroke, heart attack, and cancer).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we found a significant sex‐related difference in lean mass 10 . Therefore, in this study, we used the sex‐specific quintile of the predicted lean mass to build the trajectory model.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we found a significant sex‐related difference in lean mass. 10 Therefore, in this study, we used the sex‐specific quintile of the predicted lean mass to build the trajectory model. Otherwise, women would be in the low lean mass trajectory group, while men would account for the main component in the high lean mass trajectory group, resulting in a sex bias.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations